Abordagem estratégica das ações integradas de segurança, meio ambiente e saúde (SMS) e de responsabilidade social corporativa (RSC) - Andrade, Renata Miranda (2010)
This dissertation proposes a strategic approach for CSR - Corporate Social Responsibility - in the context of HSE - Health, Security and Environment aiming to build a systematic that allows integration of their actions so as to fulfill simultaneously legal aspects and stakeholders demands for corporate management. It intends to point out existing gaps in integrated management, as well as the benefits that the integration of CSR and HSE can bring for both company and stakeholders, such as: higher productivity, less activities overlapping and higher cohesion amongst corporate strategic objectives. As for the methodology adopted, this dissertation is a constructivist and phenomenological research, done with exploratory, bibliographical and documental resources in order to provide a conceptual comparison related to management of CSR and HSE by Petrobras. As a conclusion, a knowledge basis that allows an approach in strategic level for concept development and a discussion about the limits of HSE in the context of company dynamics should be accomplished, pointing out the paths for model selection and implementation. As a result, it is expected that the dissertation helps to consolidate an alternative proposal in the context of information related to CSR and HSE management, supporting new insights about the benefits brought by integration of both issues